Study on surface deformation induced by shield excavation due to coarse particle content in strongly weathered rock layers - Puzhen An; Baoxin Jia; Qinglei Yuan; Lei Chen (PLoS ONE, 2025)
Currently, there is limited research focusing on the surface deformation caused by shield excavation in strongly weathered rock formations with significant coarse particle content. This study, based on the shield tunnel project of the Pearl River Delta Intercity Pazhou Branch Line, investigates the influence of coarse particle content in strongly weathered rock layers on their mechanical properties, as well as its effect on surface subsidence during tunnel shield excavation. By comparing Peck’s formula with random medium theory, the study expands the application of random medium theory in engineering, converting many of Peck’s empirical parameters into corresponding parameters within the random medium framework. Additionally, Peck’s formula is modified to account for the coarse particle content in strongly weathered rock layers. The results show that as the coarse particle content increases, the force transmission mechanism in the strongly weathered rock shifts from compressive deformation typical of fine-grained soils to point-contact force transmission between coarse particles. Furthermore, as the coarse particle content rises, the strata loss rate tends to decrease gradually. The final settlement curve, calculated using the method that considers changes in coarse particle content, is closer to the measured values. This study’s calculation method more accurately reflects the surface deformation behavior caused by shield tunnel construction in strongly weathered rock layers, particularly when coarse particle content is taken into account. It also provides a better understanding of the combined impact of various construction parameters as the coarse particle content changes during the excavation process.